Networks of interaction and functional interdependence in societies across the Intermediate Area - Martín, Alexander J. (2014)
This article explores the role that a community’s network of interaction—an intrinsic feature of the degree of nucleation or dispersal of communities—played in the differential development of societies across the Intermediate Area (Northern South America and Southern Central America). We propose that large nucleated communities, where domestic units have access to larger networks of household interaction, facilitate the development of more functional interdependent social institutions, while the small network of household interaction inherent to smaller villages and dispersed populations encourages functional redundancy in domestic units. To test these expectations, the compositions of communities in three prehistoric populations are compared through the use of multivariate icons (graphical depictions of the variation in artifact types for different household samples). The results indicate that more nucleated settlements have more pronounced indicators of functional interdependence within their constituent units.